1998
DOI: 10.1021/la971317o
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Barriers in the Kinetics of Water Vapor Adsorption/Desorption on Activated Carbons

Abstract: The adsorption of water vapor on a highly microporous coconut-shell-derived carbon and a mesoporous wood-derived carbon was studied. These carbons were chosen as they had markedly different porous structures. The adsorption and desorption characteristics of water vapor on the activated carbons were investigated over the relative pressure range p/p° = 0−0.9 for temperatures in the range 285−313 K in a static water vapor system. The adsorption isotherms were analyzed using the Dubinin−Serpinski equation, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
163
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(197 citation statements)
references
References 22 publications
(54 reference statements)
32
163
2
Order By: Relevance
“…The Boehm titration method can be used to determine the number of oxygen-containing groups on a sample surface (Müller et al 1996;Jorge et al 2002). Thus, 1 g samples of a given activated carbon was weighed carefully and placed into vials containing 50 ml of a 0.05 mol/l solution of hydrochloric acid, sodium hydroxide, sodium carbonate and sodium bicarbonate, respectively.…”
Section: Boehm Titrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Boehm titration method can be used to determine the number of oxygen-containing groups on a sample surface (Müller et al 1996;Jorge et al 2002). Thus, 1 g samples of a given activated carbon was weighed carefully and placed into vials containing 50 ml of a 0.05 mol/l solution of hydrochloric acid, sodium hydroxide, sodium carbonate and sodium bicarbonate, respectively.…”
Section: Boehm Titrationsmentioning
confidence: 99%
“…Since the water molecule has strong permanent dipole moments, its adsorption would be significantly enhanced by introducing oxide groups onto the sorbent surface. Many researchers (Salame and Bandosz 1999;Salame et al 1999;Müller et al 1996;Jorge et al 2002) have reported that the amount of water vapour adsorbed may be improved via surface oxidation of the activated carbons. Some researchers (McCallum et al 1999;Groszek and Aharoni 1999) have discussed the adsorption mechanism of the water vapour onto active carbons and have stated that water molecules first adsorb onto oxygenated surface sites via hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 -55 Harding et al 56 analysed the existence of diffusion barriers in the kinetics of water adsorption/desorption on activated carbons. Others 30,57 have studied the kinetics of adsorption with relative water vapour pressure, in terms of a rate constant.…”
Section: Adsorption Of Water Vapourmentioning
confidence: 99%
“…This behaviour agrees fairly well with the results obtained in the literature. 30,56,57 In the low relative pressure region, the rate constant value decreases as the adsorption over the active centres proceeds and extent of covering increases, due to diffusion limitation of water molecules through the narrow micropores partially filled after adsorption on primary centres. D22G98 shows the highest rate constants at low relative pressure (up to p/p o < 0.4), probably due to the absence of the effect of diffusion of water vapour throughout the micropores, given the lack of porous structure of this sample.…”
Section: Adsorption Of Water Vapourmentioning
confidence: 99%